2016
DOI: 10.1097/yco.0000000000000253
|View full text |Cite
|
Sign up to set email alerts
|

Influence of legal status on the uptake of cannabis in young people

Abstract: Recent findings:There are significant concerns that ongoing policy changes in favour of legalisation will increase the uptake of cannabis by young people. Evidence to support a causal effect of cannabis policy changes on increased uptake by young people is lacking; more time may be needed to assess the impact because the policies are still evolving. Policy changes in favour of legalisation were associated with reduced risk perception although this may be a cause or consequence. The need to situate the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Recent trends favouring liberalization of cannabis have raised concerns about its increasing availability, and the consequences for children and adolescents for whom the early and heavy use remains associated with negative outcomes . Although current liberalization efforts have targeted adults only, many have argued that these vulnerable underage populations may also be affected indirectly, as both the supply (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent trends favouring liberalization of cannabis have raised concerns about its increasing availability, and the consequences for children and adolescents for whom the early and heavy use remains associated with negative outcomes . Although current liberalization efforts have targeted adults only, many have argued that these vulnerable underage populations may also be affected indirectly, as both the supply (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Dirisu et al found no conclusive evidence that cannabis legalisation for medical or recreational purposes increases cannabis use by young people. 20 In the two meta-analyses, Sarvet et al found that the implementation of medical cannabis policies in the USA did not lead to increases in the prevalence of past-month cannabis use among adolescents 21 and Melchior et al found a small increase in use following recreational legalisation that was reported only among lower-quality studies. 22 Given increasing interest in quantifying the impact of drug law reform, as well as a lack of systematic assessment of outcomes beyond adolescent cannabis use to date, we conducted a systematic review of original peer-reviewed research evaluating the impacts of (a) legal regulation and (b) drug decriminalisation on drug availability, use or related health and social harms.…”
Section: Introductionmentioning
confidence: 99%
“…Dirisu et al found no conclusive evidence that cannabis legalisation for medical or recreational purposes increases cannabis use by young people. 20 In the two meta-analyses, Sarvet et al found that the implementation of medical cannabis policies in the USA did not lead to increases in the prevalence of past-month cannabis use among adolescents 21 and Melchior et al found a small increase in use following recreational legalisation that was reported only among lower-quality studies. 22 …”
Section: Introductionmentioning
confidence: 99%
“…While harm to the newborn due to opioid use in pregnancy (eg, neonatal abstinence syndrome) is well documented and widely known, less is known about the negative health consequences of marijuana use during pregnancy. This fact raises concern given that changes in policy around marijuana use may result in an increase in social acceptability and a decrease in perceptions of harm . This increasing trend has been evidenced among newborns in Colorado where there have been substantially more marijuana‐exposed infants after the legalization of marijuana .…”
Section: Discussionmentioning
confidence: 99%
“…This increasing trend has been evidenced among newborns in Colorado where there have been substantially more marijuana‐exposed infants after the legalization of marijuana . Misconceptions about marijuana or cannabis use abound and include beliefs that marijuana is beneficial and nonaddictive . Anecdotally, women have been known to use marijuana to combat nausea and lack of appetite during pregnancy.…”
Section: Discussionmentioning
confidence: 99%